A qualitative study on stakeholders' views on the participation of pregnant women in the APOSTEL VI study: a low-risk obstetrical RCT - Indira S. E. van der Zande; Rieke van der Graaf; Martijn A. Oudijk; Elsbeth H. van Vliet-Lachotzki; Johannes J. M. van Delden (BMC, 2019)
Abstract Background Bioethicists argue that inclusion of pregnant women in clinical research should be more routine to increase the evidence-base for pregnant women and foetuses. Yet, it is unknown whether pregnant women and others directly involved are willing to be routinely included. Therefore, we first need to establish what these stakeholders think about research participation in regular pregnancy-related research. However, studies on their views are scarce. In our study, we piggy-backed on a relatively conventional RCT, the APOSTEL VI study, to identify the views of stakeholders on inclusion of pregnant women in this study. Methods We conducted a prospective qualitative study using 35 in-depth semi-structured interviews and one focus group. We interviewed pregnant women (n = 14) recruited for the APOSTEL VI study, in addition to healthcare professionals (n = 14), Research Ethics Committee members (RECs) (n = 5) and regulators (n = 7) involved in clinical research in pregnant women. Results Three themes characterise stakeholders' views on inclusion of pregnant women in the APOSTEL VI study. Additionally, one theme characterises stakeholders' interest in inclusion of pregnant women in clinical research in general. First, pregnant women participate in the APOSTEL VI study for potential individual benefit and secondarily for altruistic motives, contrary to hypothetical studies. Second, a gatekeeping tendency hampers recruitment of pregnant women who might be eligible and willing, and questions about pregnant women's decisional capacities surface. Third, healthcare professionals sometimes use the counselling conversation to steer pregnant women in a direction. Fourth, all stakeholders are hesitant about inclusion of pregnant women in clinical research in general due to a protective sentiment. Conclusions Pregnant women are willing to participate in the APOSTEL VI study for potential individual benefit and altruistic motives. However, an underlying protective sentiment, resulting in gatekeeping and directive counselling, sometimes hampers recruitment in the APOSTEL VI study as well as in clinical research in general. While bioethicists claim that inclusion of pregnant women should be customary, our study indicates that healthcare professionals, regulators, RECs and pregnant women themselves are not necessarily interested in inclusion. Advancing the situation and increasing the evidence-base for pregnant women and foetuses may require additional measures such as investing in the recruitment and feasibility of RCTs and stimulating pregnant women's decisional capacities.